Mythical and linguistic interpretation of the sign point inside the circle - Khassenov, B.R.; Nefedovа, L.А.; Аdilovа, А.S. (KU publ., 2020)
The article is devoted to the hypotheses of S. Qondybai about the archetype sign and sound, which are perceived as changes in Kazakh humanitarian science. S. Qondybai «The Head of Kazakh Mythology» during his short life has made great changes in Kazakh science. He connected several scientific paradigm and made many discoveries in the field of mythology and linguistics. Especially, his opinion of archetypal sounds should not remain out of the researchers’ sight. Turcologist researchers define an archetypal sound at the beginning of a word through sounds that are found in records of written culture of the Ancient and Middle Turkish period. And also, consider the sound «j» is an archetype, comparing with modern Turkish languages and dialects. Some researchers disagree with this and consider the affricate «dzh» (дж) to be original. Modern researchers hold the view of affricates «tch» (ч) and «ts» (ц) — as former affricates in the languages of the Western and Eastern Hun. And the mythologist S. Qondybai developed his opinion of archetypal sounds in a completely different direction. He took into account the opinion of O. Suleimenov «the original sign — is the sign of the point inside the circle», all alphabetical signs begin with this sign. «At the same time, proved that this sign is connected not only with the Sun, but also showed a new example of reading. He called this sign «abak» (lattice) and marked this sound, a sign of Ң (Ng). He linked the name of this sign to the fact that mankind is born having made this sound. That is, in his opinion, the original sound — Ң (Ng). In this scientific article, the authors tried to give a complete description of these ideas, and to order an original understanding, reading of the symbol point inside the circle S. Qondybai.
Шеңбер ішіндегі нүкте таңбасының мифтік-лингвистикалық интерпретациясы
Мифо-лингвистическая интерпретация символа «круг с точкой»
Keywords: archetype sound; sign; sound; circle; point; essence; language sign; moon; sun